PAIRS Annual Meeting 2020
DOI: 10.1055/s-0041-1729018
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Rotational Thrombectomy for the Management of Thrombosed Arteriovenous Shunts

Abstract: 2019, eight patients (two with previous aortic bare metal stenting, five with KS, and one with unilateral common iliac artery covered stent) were diagnosed with intermittent claudication and treated with CERAB technique. Lesion morphology was evaluated by the computed tomography angiography. All lesions were 2 TASC II B, 3 TASC II C, and 3 TASC D lesions. FU consisted of clinical assessment and duplex ultrasound at 1, 3, and 6 months of FU. Patency rates and clinically driven target lesion revascularization we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The rotational thrombectomy system can be successfully used to treat patients with aneurysmal AVF. Other groups have shown that the CLEANER device can be a safe and effective bail-out option in restoring patency to thrombosed AV shunts not responding to balloon thrombectomy methods ( 52 ). One technical caveat is that the CLEANER device does not advance over a wire.…”
Section: Endovascular Thrombectomy Techniques and Outcomesmentioning
confidence: 99%
“…The rotational thrombectomy system can be successfully used to treat patients with aneurysmal AVF. Other groups have shown that the CLEANER device can be a safe and effective bail-out option in restoring patency to thrombosed AV shunts not responding to balloon thrombectomy methods ( 52 ). One technical caveat is that the CLEANER device does not advance over a wire.…”
Section: Endovascular Thrombectomy Techniques and Outcomesmentioning
confidence: 99%